Recent progress with electrocatalysts for urea electrolysis in alkaline media for energy-saving hydrogen production - Sun, Xiujuan; Ding, Rui (Catalysis science & technology, 2020)
The clean and renewable "hydrogen energy economy" era is coming. In this regard, the pathway for hydrogen production is of utmost importance. Recently, diligent urea (CO(NH 2 ) 2 ) electrolysis has been explored as a promising energy-saving avenue for sustainable hydrogen production in comparison with conventional water (H 2 O) electrolysis because of the low cell voltage, remediation of urea-rich wastewater and abundant electrocatalysts. Numerous non-precious materials (especially nickel-based ones) show potential as electrocatalysts for urea electrolysis in alkaline media and massive efforts are underway to improve the kinetics and thermodynamics. In this review, we firstly introduce the fundamentals of the energy-saving urea electrolysis system. Next, the recent advances with electrocatalysts for urea electrolysis are summarized. Then, the relationship between structure and activity is discussed. Finally, the remaining challenges and the future outlook are pointed out for the development of advanced bifunctional electrocatalysts, new approaches for catalyst synthesis, solar-driven urea electrolysis and electrocatalytic mechanisms for Ni-free catalysts. Urea electrolysis is a promising energy-saving avenue for hydrogen production owing to the low cell voltage, wastewater remediation and abundant electrocatalysts.